Pro12Ala Polymorphism in the Peroxisome Proliferator-Activated Receptor-gamma (PPAR gamma) Gene in Inflammatory Bowel Disease - (:unkn) unknown (MEDICAL UNIV PRESS, 2008)
Background & Aims. Peroxisorne proliferator-activated receptor-gamma (PPAR-gamma) has recently been implicated as an endogenous regulator of cellular proliferation and inflammation. Impaired expression of PPAR-gamma in colonic epithelial cells in ulcerative colitis (UC) and increased expression in hypertrophic mesenteric adipose tissue in Crohn's disease (CD) have been reported. Furthermore, PPAR-gamma ligands have been shown to inhibit tissue injury associated with immune activation in UC. Any mutation in PPAR-gamma gene may be responsible for the increase in inflammatory mediators and hence the perpetuation of inflammation in inflammatory bowel disease (IBD) patients. One common polymorphism in PPAR-gamma gene is proline to alanine substitution (Pro12Ala) which results from a CCA to GCA missense substitution in codon 12 of exon 2 of the PPAR-gamma gene. In this study, we aimed to explore Pro12Ala polymorphism in PPAR-gamma gene in IBD in Turkish patients. Methods. 69 patients with CD, 45 with UC and 100 controls of similar age and sex were studied. Genomic DNA was isolated from peripheral blood leucocytes and mutagenically separated-polymerase chain reaction (PCR) analyses were performed to determine the Pro12Ala polymorphism of the PPAR-gamma gene. Results. We observed no significant differences in the frequency of the Pro12Ala polymorphism in the PPAR-gamma gene among subjects with CD, UC and controls (15.9%, 15.5% and 13%, respectively, p>0.05). Conclusion. These results Suggest that Pro12Ala polymorphism in the PPAR-gamma gene relates neither to the risk of the development of inflammatory bowel disease nor to the clinical Subtypes of CD in the Turkish Population.
Keywords: PPAR gamma; Pro12Ala polymorphism; Crohn's disease; ulcerative colitis; ROSIGLITAZONE; RESISTANCE; THERAPY; COLITIS; TARGET